Procrastination, affective state, rumination, and sleep quality: investigating reciprocal effects with ambulatory assessment - Gort, Cassandra; Marcusson-Clavertz, David; Kühner, Christine (Journal of rational emotive and cognitive behavior therapy, 2021)
Procrastination is a prevalent problem among university students and associated with high long-term costs, but the short-term antecedents and consequences of procrastination are not well understood. Some related negative outcomes could be consequences as well as predictors of procrastination. The aim of the present study was to investigate possible reciprocal associations of affective, cognitive and health-related characteristics associated with procrastination on a momentary basis. Using ambulatory assessment, state procrastination, rumination, affective valence, and objective and subjective sleep quality were assessed over the course of 1 week. It was hypothesized that moments/days of more procrastination would be characterized by more concurrent positive affective valence and followed by moments/days of greater rumination and more negative affective valence, as well as poorer sleep quality the following night. These relations were assumed to be reciprocal, with more rumination, more negative affective valence and poorer sleep quality predicting procrastination, thus forming a self-perpetuating cycle. Multilevel modeling was used to analyze the data of 3797 observations from 63 university students. Contrary to hypotheses, procrastination moments were characterized by more concurrent negative affective valence. Furthermore, the analyses revealed no prospective reciprocal associations of the assessed constructs. Overall, the results do not support existing theoretical assumptions and research on antecedents and consequences of procrastination.
Published online: 06 May 2020
Gesehen am 18.08.2021